Unified Total Synthesis of Polyoxins J, L, and Fluorinated Analogues on the Basis of Decarbonylative Radical Coupling Reactions. Issue 39 (17th August 2017) - Fujino, Haruka; Nagatomo, Masanori; Paudel, Atmika; Panthee, Suresh; Hamamoto, Hiroshi; Sekimizu, Kazuhisa; Inoue, Masayuki
Abstract: Polyoxins J (1 a ) and L (1 b ) are important nucleoside antibiotics. The complex and densely functionalized dipeptide structures of1 a and1 b contain thymine and uracil nucleobases, respectively. Herein we report the unified total synthesis of1 a, 1 b, and their artificial analogues1 c and1 d with trifluorothymine and fluorouracil structures. Decarbonylative radical coupling between α‐alkoxyacyl tellurides and a chiral glyoxylic oxime ether led to chemo‐ and stereoselective construction of the ribonucleoside α‐amino acid structures of1 a –d without damaging the preinstalled nucleobases. The high applicability of the radical‐based methodology was further demonstrated by preparation of the trihydroxynorvaline moiety of1 a –d . The two amino acid fragments were connected and elaborated into1 a –d (longest linear sequence: 11 steps). Compounds1 a and1 b assembled in this way exhibited potent activity against true fungi, while only1 d was active against Gram‐positive bacteria. Abstract : On the double : The important nucleoside antibiotics polyoxins J and L were synthesized along with two fluorinated analogues by a newly developed radical‐based strategy that enabled rapid assembly of the four polyoxins in a unified fashion. Preliminary biological evaluation show the distinct antimicrobial spectra of the synthesized polyoxins.